The complete chloroplast genome sequence of a popular ornamental plant Calibrachoa hybrida (Solanaceae: Petunioideae) - Liu, Guofeng (Mitochondrial DNA B Resour, 2020)
Calibrachoa hybrida is a popular ornamental plant with colorful flowers. We present here the complete chloroplast genome sequence of C. hybrida. With a total length of 156,099 bp, it is comprised of a large single-copy (LSC) region of 86,695 bp and a small single-copy (SSC) region of 18,694 bp separated by two inverted repeats (IRs) of 25,355 bp for each. A total of 132 genes were identified, consisting of 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis using complete chloroplast genomes clustered C. hybrida together with petunia into the subfamily Petunioideae within the family Solanaceae.